A manufacturing-oriented supply chain model for imperfect quality with inspection errors, stochastic demand under rework and shortages. (April 2017) - Pal, Shilpi; Mahapatra, G.S.
Graphical abstract: Highlights: Three layer supply chain model with price and stock dependent stochastic demand. Imperfect items are produced and two types of inspection error at manufacturer end. Items undergo deterioration and shortages. Defective item received by retailer is sold at discount price or return for rework. Employ transport cost from manufacturer to retailer and return of defective items. Abstract: Supply chain model is very complex and it does not depend on only retailer or buyer-vendor. So we have developed a three layer supply chain production inventory model with a supplier, a manufacturer, and a retailer. Supplier produces raw material and sent it to manufacturer on continuous basis. But the manufacturer produces items which is not only of imperfect quality item but also have inspection error by classifying a non defective item as defective or classifying a defective item as non-defective during supplies to retailer. Thus the retailer received perfect and imperfect item. The retailer once again inspects the received items and detects the defective item. The retailer makes three different strategies to manage the defective items. Also the retailer have considered a price and stock dependent stochastic demand, where it has considered the effect of deterioration, shortages, backordered. In this paper we have optimized the integrated total cost with respect to production rate of manufacturer and the time when the item finished at retailer end. Numerical simulation is presented to provide important managerial insights and demonstrated the model numerically.